PROFESSIONALLY-APPLIED PHYSICAL TRAINING OF STUDENTS-PHYSICIANS ON THE BASIS OF MOTOR AND PSYCHOPHYSICAL PREPAREDNESS - Gubka, P.I.; Lupalo, O.V.; Kopchikova, S.G. (World of Medicine and Biology, 2012)
The possibilities of developing profeesssonally important motor and psychophysical abilities of students-physicians have been invastigated in the scientific work. It has been settled that students of medical higher school posses a low level of physical training, besides the tendency to lowering, functions of possibilities of resperatory and heart-vascular abilities to be restored is being observed. The ways of professionally applied physical training of students of medical higher schools, a set of psychophyical exercises.
Keywords: professionally applied physical preparation; breathing; functional possibilities